Secondary myeloid neoplasms after CD19 CAR T therapy in patients with refractory/relapsed B-cell lymphoma: Case series and review of literature - Zhao, Aiqi; Zhao, Mingzhe; Qian, Wenbin; Liang, Aibin; Li, Ping; Liu, Hui (Frontiers in Immunology, 2023)
Background: Several chimeric antigen receptor T cells (CAR T) targeting CD19 have induced profound and prolonged remission for refractory/relapsed (R/R) B-cell lymphoma. The risk of secondary malignancies, especially myeloid neoplasms, is of particular concern in the CAR T community, which still remains unclear. Methods: Four patients with R/R B-cell lymphoma after CD19 CAR T therapy diagnosed with secondary myeloid neoplasms (SMN) from 2 hospitals in eastern China were presented, including 3 with myelodysplastic syndrome (MDS) and 1 with acute myeloid leukemia (AML). Using single-cell RNA sequencing (scRNA-seq), we compared the cellular components of bone marrow (BM) samples obtained from one of these MDS patients and a health donor. We also provided a review of recently published literature concerning SMN risk of CAR T therapy. Results: Relevant demographic, clinical, laboratory, therapeutic and outcome data were collected and presented by chart review. In our case series, the male-female ratio was 3.0 and the median age at MDS onset was 61.25 years old (range, 50-78). Median number of previous systemic therapies was 4.5 (range, 4-5), including autologous hematopoietic stem cell transplantation (auto-HSCT) in one patient. BM assessments prior to CAR T therapy confirmed normal hematopoiesis without myeloid neoplasms. Moreover, for 3 patients with SMN in our series, cytogenetic analysis predicted a relatively adverse outcome. In our experience and in the literature, treatment choices for the patients with SMN included allogeneic hematopoietic stem cell transplantation (allo-HSCT), hypomethylating agent (HMA), period filgrastim, transfusions and other supportive care. Finally, treatment responses of lymphoma, together with SMN, directly correlated with the overall survival of this community. Of note, it appeared that pathogenesis of MDS wasn’t associated with the CAR T toxicities, since all 4 patients experienced a pretty mild CRS of grade 1-2. Additionally, scRNA-seq analysis described the transcriptional alteration of CD34+ cells, identified 13 T/NK clusters, and also indicated increased cytotoxic T cells in MDS BM. Conclusion: Our study illustrated the onset and progression of SMN after CD19 CAR T therapy in patients with R/R B-cell lymphoma, which provides useful information of this uncommon later event.